Indolent Tumour in Cervicofacial Region. Diagnosis and Comment; [Tumor Indolente en la Región Cervicofacial. Diagnóstico y Comentario] - Loubies-Muñoz, R; Aragon-Caqueo, D (Ediciones Doyma, S.L., 2024)
[No abstract available]